2020
DOI: 10.21608/ajas.2020.147362
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality of Some Sugar Cane Varieties as Affected by Har-vesting Age and Phosphorus Fertilization Levels

Abstract: The present study was conducted at district Kom Ombo sugar cane farms, (latitude of 24 o 28 o N and longitude of 32 o 57 o E), Aswan Governorate, in the two seasons of 2015/2016 and 2016/2017 including plant cane and 1 st ratoon crops, respectively. To study the effect of harvesting age and phosphorus fertilization levels on yield and quality of some sugar cane varieties. Field experiment included twenty-seven treatments represented the combinations among three harvesting ages (10, 11 and 12 months) three phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…These results are due to the increase in sucrose % in total soluble solids % contents with increasing sugar cane age at harvest. These results are in agreement with those mentioned by (Mequanent 2016;Mehareb and Abazied 2017;Teama, et. al., 2020) who found that juice purity % was significantly influenced by the harvest ages.…”
Section: Sugar Recovery Percentsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are due to the increase in sucrose % in total soluble solids % contents with increasing sugar cane age at harvest. These results are in agreement with those mentioned by (Mequanent 2016;Mehareb and Abazied 2017;Teama, et. al., 2020) who found that juice purity % was significantly influenced by the harvest ages.…”
Section: Sugar Recovery Percentsupporting
confidence: 94%
“…al. 2016;Mequanent, 2016;Mehareb and Abazied 2017;Teama, et al, 2020;Gamechis andEbisa, 2021 andAli, et. al.…”
Section: Introductionmentioning
confidence: 99%